Variable viscosity of casson fluid flow over a stretching sheet in porous media with Newtonian heating - Ahmad, Kartini; Abdul Halim, Syafrina; Hanouf, Zahir (RGN Publications, 2018)
Casson fluid flow with variable viscosity in porous media over a heated stretching sheet is investigated. The partial differential equations representing the flow motion are first transformed to ordinary differential equations by similarity transformation before being solved numerically by the finite-difference method. The effects of the viscosity variation parameter (Ω), the permeability number (κ), Prandtl number (Pr), Biot number (Bi) and non-Newtonian fluid parameter (β) on the fluid flow and heat transfer, along with the temperature and velocity profiles, are presented graphically for some arbitrary values.